Study of structural optimization design on a certain vehicle body-in-white based on static performance and modal analysis. (1st January 2020) - Li, Shengqin; Feng, Xinyuan
Highlights: An all-aluminum vehicle body was used as an example and the finite element model of the body-in-white was established in ANSA. The bending stiffness, torsional stiffness and modal characteristics of the body were calculated, analyzed and optimized, based on the sensitivity analysis of thickness of the vehicle body structure. The body structure was optimized according to the body structure optimization, the quality was reduced by 9.2% to achieve lightweight goal. Abstract: The intensity analysis was proposed for a certain all-aluminum vehicle body-in-white, and an optimistic method of the vehicle body was carried out based on lightweight target. The finite element model of vehicle body-in-white was established, and the flexural rigidity and torsional rigidity of the vehicle body are calculated according to the actual operating conditions of the vehicle. The flexural rigidity and torsional rigidity of the vehicle body are calculated, and the main opening deformation of the vehicle body under these two working conditions was studied. Finally, based on the thickness of the body panel, the structural sensitivity analysis of the vehicle body was carried out. According to the sensitivity analysis data, the optimization variable is determined with lightweight as the target, and the vehicle body structure is optimized. The results showed that the static and dynamic performance indexes of the white body were higher than the standards of similar motorcycle type at home and abroad, the bending stiffness of the structurally improved basic model after sensitivity optimization was reduced by 2.1% compared with before optimization, but still much higher than the target reference value (122, 000 N/mm). And the quality of the vehicle body was reduced, which met the lightweight requirements of optimized design after the optimization of the thickness of the improved basic model.